IMPLEMENTASI JUAL BELI PESANAN (ISTISHNA’) PADA USAHA BENGKEL LAS YUDA DI KELURAHAN TAMBUN NABOLON - Wina Nazliya; Nurhayati; Mawaddah Irham (Program Studi Ekonomi Syariah Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2022)
Abstract Istishna’ is a contrack of orders transaction made by producers and consumers to make an item with certain specifications with a payment system that canibe done at theibeginning, at the middleior at the end. This studyiiaims to find outiihow to carryiiout transaction and how to implement orders transaction (istishna’) at the Yuda Welding Workshop. This studyiuses qualitativeimethods withidata collectionitechniques throughiobservation, interviews, andidocumentation of business owners and customers involved in orders transaction at the Yuda Welding Workshop. Theiresults showedithatithe implementationiof transactionat the Yuda Welding Workshop was in accordanceiwith the pillars and conditions of transactioniniIslam. The perpetrators of the transaction are mutually pleased, the goods being traded are clear and lawful, and the price of the goods is known by the consumer. While the implementation of orders transaction (istishna’) carried out at the Yuda Welding Workshop has not fully complied with the terms of istishna’, namely ordered goods that are notiin accordanceiwith the specificationsidesired by consumers, the occurrence of delays in the completion of the ordered goods, and not timely repayment. Payments made by consumers. However, in terms of the payment system, it is iniaccordance with theiconcept of istishna’ thatiis, at theibeginning, at theimiddle, andiat theiend.